2125. Determinants of Placental Transfer of HSV-specific Antibodies and the Impact of SARS-CoV-2 Coinfection. (15th December 2022) - Mahant, Aakash Mahant; Estrada, Fatima; Aguilan, Jennifer; Sidoli, Simone; Herold, Betsy; Herold, Betsy
Abstract: Background: Primary versus recurrent herpes simplex virus 1 or 2 (HSV-1 or HSV-2) infection during pregnancy carries a higher risk of neonatal herpes. Murine and clinical studies demonstrate that antibody dependent cellular cytotoxicity (ADCC) provides greater protection against disseminated neonatal disease. To quantify relative transfer of HSV specific Abs with different functions and targets and whether SARS-CoV-2 coinfection modified transfer, we conducted a prospective cohort study of mother-infant dyads prior to and during COVID-19. Methods: Total and HSV lysate, glycoprotein D (gD) and glycoprotein B (gB)-specific IgG, IgG1 and IgG3, nAbs and ADCC were quantified in paired 3 rd trimester maternal and cord blood. IgG1 and IgG3 subclass and gD or gB-specific Abs were isolated by column purification and glycan profiles were assessed using mass spectrometry. The pre-COVID study population included 21 term and 15 preterm dyads who were HSV seropositive and the pri-COVID cohort included 25 HSV seropositive term dyads whose mothers were also SARS-CoV-2 PCR and COVID Ab positive at delivery. Results: HSV-specific Ab and neutralizing Ab transfer ratio (TR) were higher in term compared to preterm pre-COVID dyads (all p< 0.05), but the ADCC TR was < 1.0 for both groups. To determine if the low ADCC TR reflected antigenic target, subclass and/or glycans, we enriched for anti-gD and anti-gB specific and IgG1 and IgG3 Abs. The anti-gD Abs were exclusively IgG, had only neutralizing activity and had glycans associated with FcRn binding. In contrast, anti-gB Abs were both IgG1 and IgG3; had both neutralizing and ADCC activity and expressed glycans associated with both FcRn and FcγRIIIa binding. There was no significant difference in HSV-specific IgG TR in pre-COVID vs COVID dyads (0.42) but the nAb TR was lower (p=0.018) and ADCC TR higher (p< 0.001) in COVID compared to pre-COVID patients. Placental immunohistochemistry showed an increased colocalization of FcRn and FcγRIIIA in SARS-CoV-2 positive mothers, which would favor transfer of ADCC Abs. Conclusion: Defining the determinants of ADCC transfer has implications for future vaccine and monoclonal Ab strategies to prevent/treat neonatal herpes. We speculate that increasing the transfer of ADCC may be a key element in providing immune protection Disclosures: Betsy Herold, MD, Viracor (Eurofins): Advisor/Consultant|X-Vax, Technologies: Advisor/Consultant|X-Vax, Technologies: Grant/Research Support|X-Vax, Technologies: Serve on Scientific Advisory Board for X-Vax, Technologies and receiving reserach funding for related worl. Betsy Herold, MD, Viracor (Eurofins): Advisor/Consultant|X-Vax, Technologies: Advisor/Consultant|X-Vax, Technologies: Grant/Research Support|X-Vax, Technologies: Serve on Scientific Advisory Board for X-Vax, Technologies and receiving reserach funding for related worl.